2011
DOI: 10.1007/s00253-011-3556-0
|View full text |Cite
|
Sign up to set email alerts
|

Microbial synthesis of gold nanoparticles using the fungus Penicillium brevicompactum and their cytotoxic effects against mouse mayo blast cancer C2C12 cells

Abstract: Microorganisms, their cell filtrates, and live biomass have been utilized for synthesizing various gold nanoparticles. The shape, size, stability as well as the purity of the bio synthesized nanoparticles become very essential for application purpose. In the present study, gold nanoparticles have been synthesized from the supernatant, live cell filtrate, and biomass of the fungus Penicillium brevicompactum. The fungus has been grown in potato dextrose broth which is also found to synthesize gold nanoparticles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(75 citation statements)
references
References 40 publications
2
72
0
Order By: Relevance
“…1(a) and (b) shows the UV-visible spectra of the corresponding aqueous dispersion of Au NPs obtained by using LE and SE respectively. From the above figure it is suggested that SE did not yield well dispersed NPs [13,14]. The change in the color of the gold salt solution from light yellow to purple is the clear evidence of the reduction of the gold ions to NPs as aqueous dispersion of Au NPs are known to exhibit intense color owing to the SPR phenomenon [13,14,18,19,20].…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…1(a) and (b) shows the UV-visible spectra of the corresponding aqueous dispersion of Au NPs obtained by using LE and SE respectively. From the above figure it is suggested that SE did not yield well dispersed NPs [13,14]. The change in the color of the gold salt solution from light yellow to purple is the clear evidence of the reduction of the gold ions to NPs as aqueous dispersion of Au NPs are known to exhibit intense color owing to the SPR phenomenon [13,14,18,19,20].…”
Section: Resultsmentioning
confidence: 93%
“…Hence increase in the pH to basic condition may either have decreased the formation of initial metal nuclei or may have resulted in the agglomeration of the NPs [13,38]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the large family of metal nanoparticles, AuNPs have been used in various cutting edge applications such as biology systems and medicinal industry, communication, nano-electronics, nano-sensor and environmental protection [4][5][6]. Moreover, AuNPs have a tremendous potential in biological applications such as nano-gene delivery, nano-drug delivery, biological nanosensing, biological nano-labeling and nano-medicine [7,8] along with their antifungal, antibacterial and larvicidal activities [9][10][11][12]. A plenty of techniques have been recognized to synthesize AuNPs, including conventional chemical reduction, spray pyrolysis, physical steam deposition and irradiation method.…”
Section: Introductionmentioning
confidence: 99%